STS 204Cu 스테인리스강의 저온 플라즈마 침질탄화 처리 시 CH₄ 가스 함량에 따른 경화층 (S-Phase) 거동 - 이인섭(Insup Lee); 김호준(Hojun Kim) (Biuletyn Uniejowski, 2018)
Plasma Nitriding treatment was performed on STS 204Cu stainless steel samples at a temperature of 400oC for 15 hours with varying N2 content as 10%, 15% and 25%. Regardless of the content of N2, S-Phase which is a hardened layer of Nitrogen (N) supersaturated phase, was formed in the surface of plasma treated samples. When N2 content was 25%, the thickness of the hardened layer reached up to about 7 μm and the surface hardness reached a value of 560 Hv0.05, which is about 2.5 times higher than that of untreated sample (as received 220 Hv0.05). From potentiodynamic polarization test, it was observed that compared to as received sample, the corrosion potential and the corrosion current density of the plasma treated samples were decreased regardless of the N2 content, but the corrosion resistance was not increased much due to the precipitation of Cr2N. On the other hand, pitting potential of the samples treated with 10% and 15% N2 was higher than that of as received sample, however, the samples treated with 25% exhibited a lower pitting potential. Therefore, 10% N2 content was selected as optimum plasma nitriding condition and to further increase both the thickness and surface hardness and the corrosion resistance of the hardened layer, different CH4 content such as 1%, 3% and 5% was introduced into the plasma nitriding atmosphere. With 1% CH4, the thickness of the hardened layer reached up to about 11 μm and the surface hardness was measured as about 620 Hv0.05, which is about 2.8 times that of as received sample. And the corrosion resistance of the plasma treated sample by using 1% CH4 was improved significantly due to much higher pitting potential, and lower corrosion current density. When the CH4 content was more than 1%, the thickness and surface hardness of the hardened layer decreased slightly and the corrosion resistance also decreased. KCI Citation Count: 0